Lexical Items of Flora and Fauna in Local Languages: An Ecolinguistics Study - Herman, Herman; Purba, Ridwin; Saragih, Amrin (Journal of Social Science and Humanities Research, 2022)
Ecolinguistcs study is becoming more popular year by year since many researcher, linguists, and other experts do some researches. Wendel’s (2005:51) definition of ecolinguistics formulated that the ecological approach to language takes into consideration the complex network of relations occurring between environment, languages and people speaking these languages. Since ecolinguistics related to environment, language and people speaking the language, this research is aimed to discuss about the local languages, Hokkian and Tio Cu related to the environment. The data used in this article is the lexical items for fauna and flower. After conducting small observastion, the researcher concludes that the knowledge of lexical items for flora and fauna in local languages, Hokkian and Tio Cu, is less because of environment factors. This means that the language of Hokkian and Tio Cu had been influenced by Bahasa Indonesia as national language. This happened as in the era before the year of 2000, Chinese were not allowed to use their Chinese name, languages (Mandarin or local languages), culture, etc.